Iron and Cobalt Metallotropism in Remote‐Substituted NHC Ligands: Metalation to Abnormal NHC Complexes or NHC Ring Opening. (19th September 2018) - Danopoulos, Andreas A.; Massard, Alexandre; Frison, Gilles; Braunstein, Pierre
Abstract: Metallotropism of the M[N(SiMe3 )2 ]2 metal fragment in the tautomeric systemIA R ⇌AC R involving imidazolium salts/N‐heterocyclic carbenes with remote aminide/amine substituents, respectively, is manifested by its CNHC carbophilicity (R=tBu, M=Co, Fe) or NRaminido nitrogenophilicity (R=Cy, M=Co, Fe; R=Mes, M=Fe) and has been rationalized on the basis of steric and electronic effects. The thermolysis products of the [MN(SiMe3 )2 2 ]/IA R ⇌AC R system are also substituent‐dependent, leading to a rearranged aminide‐functionalized aNHC Co2 complex of an unprecedented type or to ring‐opened metallaketenimines; they are postulated to originate from different metalloisomers. The results are interpreted on the basis of the X‐ray diffraction analysis of 11 new compounds.